2011
DOI: 10.1002/chem.201102542
|View full text |Cite
|
Sign up to set email alerts
|

A Diverted Total Synthesis of Mycolactone Analogues: An Insight into Buruli Ulcer Toxins

Abstract: Mycolactones are complex macrolides responsible for a severe necrotizing skin disease called Buruli ulcer. Deciphering their functional interactions is of fundamental importance for the understanding, and ultimately, the control of this devastating mycobacterial infection. We report herein a diverted total synthesis approach of mycolactones analogues and provide the first insights into their structure-activity relationship based on cytopathic assays on L929 fibroblasts. The lowest concentration inducing a cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 59 publications
5
92
0
2
Order By: Relevance
“…33 The present results demonstrate that 4b is only 3-fold less efficient for the binding to WASP, with an IC 50 of 97.5 ± 7.1 μM vs 32.3 ± 22.1 μM for natural mycolactone A/B ( Figure 5B and Figure 6). Compared to 5b (IC 50 = 21.5 ± 0.7 μM), addition of a (triazol-4-yl)ethanol to the core in northern position (32c) limited binding (IC 50 = 170 μM), as did the selective epimerization of C12′ and C15′ (5i, IC 50 = 100 μM) or the removal of two hydroxyl groups of the southern fragment (C13′,C15′-dideoxy 5m, IC 50 = 350 ± 70.7 μM) or one hydroxyl group in C15′ (5k, IC 50 = 250 ± 0.7 μM).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 69%
See 1 more Smart Citation
“…33 The present results demonstrate that 4b is only 3-fold less efficient for the binding to WASP, with an IC 50 of 97.5 ± 7.1 μM vs 32.3 ± 22.1 μM for natural mycolactone A/B ( Figure 5B and Figure 6). Compared to 5b (IC 50 = 21.5 ± 0.7 μM), addition of a (triazol-4-yl)ethanol to the core in northern position (32c) limited binding (IC 50 = 170 μM), as did the selective epimerization of C12′ and C15′ (5i, IC 50 = 100 μM) or the removal of two hydroxyl groups of the southern fragment (C13′,C15′-dideoxy 5m, IC 50 = 350 ± 70.7 μM) or one hydroxyl group in C15′ (5k, IC 50 = 250 ± 0.7 μM).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 69%
“…25 The chemical synthesis of natural products and their derivatives allows the biological exploration of complex systems, and programs centered on the synthesis and structural modulation of mycolactone A/B have been reported by Kishi, Altmann, and us ( Figure 2). 2 Kishi clearly opened the way to chemical modifications of this exotoxin with several generations of elegant total syntheses of mycolactone A/B and also of the 33 other eight naturally occurring mycolactones that differ only by the nature of the southern fragment. 2,9,26−30 However, the cytopathic effect (CPE, the concentration of mycolactone analogue for which 90% of the cells round up) of only the single analogue 1a was disclosed up to now (Figure 2A).…”
Section: ■ Introductionmentioning
confidence: 98%
“…Bodipy-labelled mycolactone has been detected in the cytosol of cells within 2 minutes of exposure, but interestingly is excluded from the nucleus [24,25]. Other in vivo experiments have demonstrated that mycolactone can diffuse away from the site of injection and can access all bodily compartments with the exception of the brain [26].…”
Section: Mycolactonementioning
confidence: 89%
“…Modular variants of mycolactone were synthesized as described (20,23). Stock solutions of mycolactone and variants were prepared in dimethyl sulfoxide, and then diluted 1000× in culture medium for cellular assays or 10× in PBS before injection in animals.…”
Section: Methodsmentioning
confidence: 99%